Miraculous Images and Devotional Practices in Italy at the Time of the Covid-19 Pandemic - Papasidero, Marco (Journal for the study of religion, nature and culture, 2022)
The aim of this paper is to analyse the use of Catholic miraculous images during the Covid-19 pandemic in Italy, focusing on the ways in which they have been used and the related rituals performed, especially involving movement, temporality, and nature. I take a multidisciplinary approach, based on a historical perspective, but enriched by the strong influence of anthropology and semiotics. An interesting focus emerges on the devotional practices, both online and, when possible, in presence, in which the miraculous power of historical images is rediscovered and sometimes re-elaborated in light of contemporary sensibilities. At the same time, the rituals performed by clergy constitute a complex negotiation, with the aim of imploring the miraculous power of the supernatural helper that the image represents. The devotees’ idea of a miraculous power involved in the image is itself part of the representation of their power.